1999
DOI: 10.1051/gse:19990202
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefit from using an identified major gene in BLUP evaluation with truncation and optimal selection

Abstract: -This study investigates the benefit of including information on an identified major gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…The results for a favourable linkage would be expected to be similar to those for gene-assisted selection on a trait controlled by a quantitative trait locus and polygenes e.g. [26]. In this situation, there would be an increase in the rates of genetic gain (at least in the early generations of PrP selection) and inbreeding.…”
Section: Discussionmentioning
confidence: 85%
“…The results for a favourable linkage would be expected to be similar to those for gene-assisted selection on a trait controlled by a quantitative trait locus and polygenes e.g. [26]. In this situation, there would be an increase in the rates of genetic gain (at least in the early generations of PrP selection) and inbreeding.…”
Section: Discussionmentioning
confidence: 85%
“…In general, the results can also be applied to major genes in mixed inheritance models, where a major gene has a large effect on the trait, and many background genes have small effects [4]. Villanueva et al [23] simulated schemes with a mixed model inheritance for BLUP optimum contribution selection (similar to our BLUP scheme). They found that the frequency of the favourable allele had reached 0.95 after eight generations for a gene with recessive inheritance.…”
Section: Relaxation Of Assumptionsmentioning
confidence: 99%
“…This finding is similar to the results in Figure 1, although the schemes differed considerably (the genotypic values (2.0 and dominance deviation was −0.5), initial frequency (0.15) of the non-disease allele, and size of the scheme (120 animals per generation)). In the case where a major (disease) gene and other (economic) polygenic traits are included in the breeding goal, the question arises how much weight should be given to the major gene relative to that of the polygenic traits in the short and long term [4,9,16,21,23]. This question is beyond the scope of this paper and is currently under active investigation [24,25].…”
Section: Relaxation Of Assumptionsmentioning
confidence: 99%
“…However, the vast majority of the research directed to evaluate the potential benefits of using information on identified quantitative trait loci or QTL (GAS) or on markers linked to them (MAS) in artificial selection has been focused on singletrait scenarios (e.g., Ruane and Colleau, 1995;Villanueva et al, 1999Villanueva et al, , 2002Abdel-Azim and Freeman, 2002).…”
mentioning
confidence: 99%
“…Dynamic selection tools that optimise genetic contributions of selection candidates for obtaining maximum genetic gain while constraining the rate of inbreeding (∆F) to a pre-defined value have been used under single trait scenarios with GAS or MAS (Villanueva et al, 1999. These tools are implemented as quadratic indexes in which the desired ∆F is achieved by applying a quadratic constraint on the average coancestry of selection candidates weighted by their projected use .…”
mentioning
confidence: 99%